Implementasi Green Accounting, Profitabilitas dan Corporate Social Responsibility pada Nilai Perusahaan - Dewi, Putu Purnama; Edward Narayana, I Putu (E-Jurnal Akuntansi; Vol 30 No 12 (2020)DO - 10.24843/EJA.2020.v30.i12.p20, 2020)
The purpose of this study is to determine the effect of the implementation of green accounting, profitability, and corporate social responsibility on firm value. The sample of this study is mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2015 - 2019. The data used are secondary data in the form of environmental cost, return on equity, CSR Index, and Tobins'Q. The data is obtained from the Indonesia Stock Exchange website and related company websites. The results of this study indicate that the effect on green accounting has a positive effect on firm value, this is obtained from a significance value of 0.003 with a beta coefficient value of 0.228. Profitability also has a positive influence on firm value is a positive influence, this is indicated by a significance value of 0.000 with a beta coefficient value of 0.724. The effect of corporate social responsibility on firm value also shows a positive direction, as indicated by a significance value of 0.011 with a positive beta coefficient value of 0.210. Keywords: Green Accounting; Profitability; Corporate Social Responsibility;  Firm Value.